Brandishing Cyberattack Capabilities - Libicki, Martin C. (RAND Corporation, 2013)
Deterrence is possible only when others have at least a good idea of possible U.S. military reprisals, but cyberattack capabilities resist such demonstration. This report explores ways they can be and under what circumstances, then goes on to examine the difficulties and the drawbacks. Such "brandishing" is no panacea and could even backfire if misinterpreted. Its success also relies on the strength of other elements of the deterrence posture.